Microbiological techniques (Steamboat Springs, Co : Center for Visual Imaging, 1986)
The various sterile techniques involved in the inoculation,transfer and growth of microrganism are described and illustrated. Included are special techniques such as streak plating, pour plating, serial dilution and pipeting.Review questions are included in the supplement to test or reinforce learning.
Keywords: Microbiological -- laboratory manuals